2021
DOI: 10.1007/s40670-021-01421-9
|View full text |Cite
|
Sign up to set email alerts
|

Tutor–Student Partnership in Practice OSCE to Enhance Medical Education

Abstract: Background Training of examiners is essential to ensure the quality of objective structured clinical examination (OSCE). We aimed to study a perceived effectiveness of tutor-student partnership in a practice OSCE module by novice OSCE tutors and medical students. Method We implemented a practice OSCE at a medical faculty in France with novice tutors and third year medical students as partners. Each tutor (n = 44) served as a partner for the group of 5 students in the conception of the scenario and as an evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In a qualitative study conducted in Switzerland on a sample of 15 SPs from 8 nursing schools and medical schools, SPs reported motivation and interest to participate in pedagogical activities, and at the same time highlighted the importance of supportive work conditions [21]. Recently, we have shown that the partnership between learners and their educators in the elaboration of pedagogical tools is bene cial for both learning and teaching [22].…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study conducted in Switzerland on a sample of 15 SPs from 8 nursing schools and medical schools, SPs reported motivation and interest to participate in pedagogical activities, and at the same time highlighted the importance of supportive work conditions [21]. Recently, we have shown that the partnership between learners and their educators in the elaboration of pedagogical tools is bene cial for both learning and teaching [22].…”
Section: Introductionmentioning
confidence: 99%